Believing is seeing: Development and validation of the STRESS (Subjective Thoughts REgarding Stress Scale) for measuring stress beliefs. (May 2022) - Kilby, Christopher J.; Sherman, Kerry A.; Wuthrich, Viviana M.
Abstract: The association between stress beliefs and stressor appraisals has been limited by the absence of a comprehensive stress belief scale. This paper aimed to develop a new stress belief scale (the Subjective Thoughts REgarding Stress Scale; STRESS) and to assess the association between stress beliefs and stressor appraisals. Study 1: A pool of 75 Likert-type items assessing beliefs about stress and cognition, emotion, social factors, and behavior, was piloted on an international sample ( N  = 107); all items were found to reflect commonly held beliefs. Study 2: Exploratory factor analysis ( N  = 419), reduced the scale to 19 items over three factors (Consequences, Social Factors, and Coping Efficacy), demonstrating acceptable construct validity and internal reliability. Study 3: Confirmatory factor analysis ( N  = 300) replicated the factor structure in a new sample and demonstrated acceptable convergent and divergent validity. Study 4: Predictive validity ( N  = 137) was demonstrated with stressor appraisals and acceptable test-retest reliability over two weeks. This study provides evidence for both good psychometric properties of the new STRESS measure and predictive validity in terms of an association between stress beliefs and stressor appraisals. Highlights: Current stress belief measures do not correlate with stressor appraisals. Current stress belief measures may have flaws in their development. This four-study paper reports the development of a new measure, the STRESS. The STRESS demonstrated satisfactory psychometric requirements. The STRESS predicted five types of stressor appraisals of a stress induction.